Botulinum Neurotoxins and Nervous System Future Challenges for Novel Indications - Luvisetto, Siro (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book collects 25 scientific articles from laboratories around the world, all of which use botulinum neurotoxins as the main protagonists of their studies. The use of botulinum neurotoxin in medicine, following its ability to inhibit the effects of various disorders of different etiology on the human organism, constitutes the main topic of each article presented here. This book, which is aimed at both students and medical professionals, attempts to summarize current knowledge about the use of botulinum toxin as a therapeutic agent in many diseases, ranging from spasticity to tremor, form motor dysfunction after stroke to neuropathic pain, from hyperactive muscle to migraine, and so on. Thanks to its simplified writing, accessible to an audience who may not be familiar with the mysteries of science, readers will get new insights into this biological toxin and its multiple applications, not simply relegated to its historical use to correct of face wrinkles. Both review and research articles are presented, not only concerning animal studies, but also clinical reports. This book will provide an up-to-date picture of the state-of-the-art of the possible development of novel applications of botulinum neurotoxins for future therapeutic purposes.